The Effect of Stocking Density of Eel (Monopterus albus) Reared In Mud Media on Growth And Survival - Abdul Rahman Siregar; Niken Ayu Pamukas; Iskandar Putra (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study aims to know the effect of stocking density of eel (Monopterus albus) reared in mud media on growth and survival. The research was carried out in March 3, 2020 - April 12, 2020 at the Fish Hatchery Unit, Faculty of Fisheries and Marine, Riau University. The test animals in this study were rice field eels (Monopterus albus) with a size of 14 cm - 16 cm, as many as 252 animals were spread into 12 buckets. Using experimental method of completely randomized design (RAL), one factor with four treatments and three replications. The treatments were different stocking density P1 = 200 ind/m3, P2 = 300 ind/m3, P3 = 400 ind/m3, P4 = 500 ind/m3. The results showed that of eel (Monopterus albus) stocking density reared in mud media had a significant effect (P <0.05) on absolute weight growth, specific growth rate, feed conversion ratio but had no significant effect on survival (SR). The best treatment was at stocking density P1 200 ind/m3 with an absolute weight yield of 6.96 g, absolute length 8.96 cm, specific growth rate 2.35%, feed conversion ratio (FCR) 1.23, and survival (SR). 80.55%. The range of water quality during the study, namely, temperature 27-29.9ºC, pH 6-7, dissolved oxygen 6.17.4 mg / L, and ammonia ranged from 0.03-0.06 mg / L.